ANALISIS PENGARUH EFEKTIVITAS DAN EFISIENSI KEUANGAN DAERAH TERHADAP DERAJAT DESENTRALISASI FISKAL DENGAN MEDIASI PERTUMBUHAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA PEKANBARU PERIODE 2011-2020 - Helly Aroza Siregar (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The purpose of this study is to analyze the level of financial effectiveness and efficiency and to analyze the direct and indirect effects of these variables on fiscal decentralization, mediating by the growth of PAD in Pekanbaru City from 2011 to 2020. The method of data analysis is descriptive statistical analysis and path analysis. The results of the study show that in the last decade the Pekanbaru City Government's financial performance had been in the